Associations between pregnancy complications and incident cardiovascular disease: a nationwide data linkage study in Wales. (3rd October 2022) - Al Bahhawi, T; L Harrison, S; A Lane, D; Buchan, I; Skjoth, F; Sharp, A; Abbasizanjani, H; Akbari, A; Torabi, F; Halcox, J; Lip, G Y H
Abstract: Background: Previous studies have associated pregnancy complications with a higher risk of cardiovascular disease. However, previous studies have not sufficiently evaluated the impact of broad range of pregnancy complications or common cardiovascular conditions individually. Furthermore, most previous studies have relied on data from hospital admission records only, which may not have adequately accounted for conditions that may not result in an inpatient hospital admission, such as atrial fibrillation. Purpose: To examine the risk of ischemic heart disease (IHD), stroke, atrial fibrillation or heart failure among women after their first pregnancy with a history of pregnancy complications compared to women without pregnancy complications in a large nationwide study using linked routinely collected data. Methods: A retrospective cohort study was conducted using the Secure Anonymised Information Linkage (SAIL) Databank and included women aged 16–45 years who had their first pregnancy between 2000 and 2018 in Wales. Data were extracted from various sources such as Office for National Statistics (ONS) birth and death extracts, hospital admission, outpatient, emergency department and General Practice data sources, and pregnancy related data such as maternal indicators and national community child health. Survival analyses were conducted using Cox proportional hazard regression models adjusted for hypertension, diabetes, hyperlipidaemia, congenital and valvular heart diseases, multifetal pregnancy ethnicity, maternal age, calendar year of first birth and index of multiple deprivation. Results: A total of 298, 515 women were included in the study, of which 74, 832 (25.1%) had a history of any pregnancy complication during their first pregnancy. During a median of 9.7 years follow-up time, 2, 484 women developed at least one cardiovascular condition. Among women with a history of pregnancy complication in their first pregnancy, IHD had the highest incidence rate at 4.94 (95% confidence interval (CI) 4.44–5.49) per 10, 000 person-years, and atrial fibrillation was the lowest at 1.92 (95% CI 1.62–2.28). The history of any pregnancy complication during the first pregnancy was associated with a higher risk of all cardiovascular conditions examined, including heart failure [hazard ratio (HR) 1.93 95% CI 1.61–2.31)], IHD [HR 1.82 (95% CI 1.58–2.10)], stroke [HR 1.39 (95% CI 1.20–1.61)] and atrial fibrillation [HR 1.33 (95% CI 1.08–1.65) (Figure 1). Conclusion: This population-scale study used anonymised individual-level linked data from multiple routinely collected data sources. A history of pregnancy complications during first pregnancy was associated with a higher risk of incident cardiovascular conditions, including heart failure, ischaemic heart disease, stroke and atrial fibrillation. Applying primary preventive measures and risk assessments for cardiovascular disease after the first pregnancy may mitigate the higher risk among these women. Funding Acknowledgement: Type of funding sources: Other.